Experimental research of withdrawal of oil remains from the used “KOLLAN” oil filters - Holik, Yury; Ganoshenko, Elena (Lviv Politechnic Publishing House, 2017)
This article provides the results of research of withdrawal of oil remains as a valuable resource from the filter elements of used oil filters in order to reuse them. The possibility of effective utilization (recycling) of the used filter paper with reduced capacity of ambient air is also considered in the research.
Keywords: Utilization (recycling); used oil filter; waste